Exploring a dialogic approach in tackling psychotic diseases: A systematic review - Fernández-Villardón, Aitana; García-Carrión, Rocío; Racionero-Plaza, Sandra (Anales de Psicología / Annals of Psychology, 2022)
Psychosis is a severe mental disorder traditionally treated from a purely biological approach, which often has led to a dehumanisation in psychiatric hospitals. To counteract this trend and aiming at tackling the disease with a more human approach, psychosocial interventions have increased. In this vein, interventions based on a dialogic approach, with specific features such as egalitarian dialogue, foster psychological and social transformations in different contexts. This review aims to analyse the clinical and social effects of psychological interventions based on these principles when treating patients with psychosis. A systematic review has been carried out, following PRISMA recommendations, in the Web of Science, Scopus and PsycInfo databases. After applying the inclusion criteria, thirteen empirical studies were selected and analysed, including a quality assessment. These studies show that when introducing a dialogic approach in treating psychosis, positive clinical and relational outcomes are obtained. Likewise, patients value positively these collaborative environments, where they feel listened and understood. Whereas dialogism emerges as a tool with potential benefits to tackle psychosis, more studies are needed to clearer determine the influence of specific dialogic features on improving psychotic patients’ mental health.